Extreme ultraviolet probing of laser imprint in a thin foil using an x-ray laser backlighter - Kalantar, D; DaSilva, L; Glendinning, S; Remington, B; Weber, F; Weber, S; Key, M; Kim, N; Neely, D; Wolfrum, E; Zhang, J; Wark, J; et al. (1997)
For direct drive inertial confinement fusion, a capsule is imploded by directly illuminating the surface with laser light. Beam smoothing and uniformity of illumination affect the seeding of instabilities at the ablation front. We have developed a technique for studying the imprint of a laser beam on a thin foil using an x-ray laser as an extreme ultraviolet (XUV) backlighter. We use multilayer XUV optics to relay the x-ray laser onto the directly driven foil, and then to image the foil modulation onto a charged coupled device camera. This technique allows us to measure small fractional variations in the foil thickness. We have measured the modulation due to imprint from a low intensity 0.35 mu m drive beam incident on a 3 mu m Si foil using an yttrium x-ray laser on Nova. We present results from a similar technique to measure the imprinted modulation due to a low intensity 0.53 mu m drive beam incident on a 2 mu m Al foil using a germanium x-ray laser at the Vulcan facility. (C) 1997 American Institute of Physics.